A study of dermoscopic patterns of Wickham’s striae in lichen planus - S., Nandini A.; Zacharias, Mariet (International Journal of Research in Dermatology, 2022)
Background: Wickham striae corresponds to fine white or gray lines or dots seen on the top of the papular rash and oral mucosal lesions of lichen planus. The documented types of Wickham’s striae dermoscopic patterns are linear, reticular, circular, globular, star-burst, radial and leaf-like. Aim was to study and describe the dermoscopic patterns of Wickham’s striae in lichen planus. Methods: A prospective study was conducted between December 2019 to March 2020, among outpatients in the department of dermatology, venereology and leprosy in a tertiary care hospital. The lichen planus lesions including Wickham striae pattern were visualised with the dermatoscope (DermLite DL 4) and documented. Results: The 20% had the circular pattern, 10% radial streaming, 4% leaf venation and 2% starry sky appearance. Other pattern observed were linear which was seen in 6% of the patients. They were seen associated with lesions over the lip. Vascular patterns were noted only in 20% of the patients with most of them having dotted patchy type of vessels. Conclusions: With dermoscopy, the Wickham’s striae are the diagnostic key to differentiate lichen planus from other papulosquamous disorders. In our study we were able to see various patterns of Wickham’s striae including a less reported form like leaf venation.